2008
DOI: 10.1021/jf800175a
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Induces Apoptosis through ROS-Dependent Mitochondria Pathway in HT-29 Human Colorectal Carcinoma Cells

Abstract: trans-Resveratrol is a polyphenol found in blueberries, grapes, and wine with cancer chemopreventive properties. The low bioavailability of this compound enhances its concentration in the luminal content and becomes a potential chemopreventive agent against colon cancer. In the present study, the antiproliferative and pro-apoptotic effects on the human colorectal carcinoma HT-29 cells as well as the mechanisms underlying these effects were examined. Proliferation, cytotoxicity, and apoptosis were measured by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(127 citation statements)
references
References 32 publications
8
118
0
1
Order By: Relevance
“…Recent evidence has demonstrated that ROS serve as messengers for normal signal transductions at lower concentrations; at higher concentrations, however, they become toxic and induce cell death through various signaling pathways (8,22). As cancer cells contain higher level of ROS than normal cells, they can be easily poisoned by the phytochemical targeting ROS metabolism (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has demonstrated that ROS serve as messengers for normal signal transductions at lower concentrations; at higher concentrations, however, they become toxic and induce cell death through various signaling pathways (8,22). As cancer cells contain higher level of ROS than normal cells, they can be easily poisoned by the phytochemical targeting ROS metabolism (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Alantolactone, a sesquiterpene lactone compound, has been reported to possess antifungal, antibacteria, and antihelminthic properties. Very recently, it has been shown to induce ROS generation and apoptosis in HL-60 cells (22). However, the exact role of ROS in cell death induced by alantolactone has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that natural bioactive compounds targeting ROS metabolism can selectively kill cancer cells by increasing the ROS level above a toxic threshold. As cancer cells contain higher levels of endogenous ROS, the toxic threshold can easily be achieved in cancer cells by targeting them with exogenous ROS-generating phytochemicals [1,7,8] . Prostate cancer cells have been reported to contain higher level of ROS [9] ; therefore, targeting ROS metabolism in prostate cancer cells may be an effective treatment.…”
Section: Original Articlementioning
confidence: 99%
“…Resveratrol is an established cytotoxic agent in prostate, 23 breast, 33 ovarian, 34 colon, 35 lung, 36 heptatic, and brain cancer cells 37 and is a proposed chemopreventive agent. 22 As a component of grape skins, resveratrol is already in the diet, 38 implying it may be well tolerated if used in long-term clinical dosing.…”
Section: U0126 Inhibits Resveratrol Induced Apoptosismentioning
confidence: 99%